New Metronidazole Derivative and Some of its Complexes with Antibiofilm Study - Safaa Mahmoud, Simaa; Mohammed Noori Khaleel, Asmaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Synthesis of a new ligand, namely [bis(2-(2-methyl-5-nitro-1H-imidazol-1-yl)ethyl) hydrogen borate] (BIB), utilizing the reaction of metronidazole with boric acid in a (2:1) mole ratio The metal complexes were synthesized utilizing the reaction of (NiCl2.6H2O and CuCl2 .2H2O) with (BIB) ligand in a 2:1 (L:M) mole ratio. All synthesized compounds were characterized utilizing spectroscopic techniques such as infrared (FTIR), nuclear magnetic resonance of protons(1H NMR), ultra violet and visible radiation (UV-Vis), thermal analysis (TG), atomic absorption (A.A.S.), micro elemental analysis (C.H.N.S.), melting point (m.p.), magnetic susceptibility, molar conductivity, and chloride content measurements. All complexes were paramagnetic and electrolyte, and the suggested geometries were the tetrahedral of nickel and the distorted octahedral of copper complexes. Against the Gram-negative bacterium Pseudomonas auroginosa (G-), all synthesized compounds were evaluated as anti-biofilm agents. Strikingly, the copper (II) complexes tested exhibit significant activity against biofilms and were better at removing biofilms than metronidazole (an antibiotic that is currently used to treat infections), ligand (BIB), and nickel (II) complexes.